2018
DOI: 10.3390/v10110651
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Rift Valley Fever Virus Aerosol Infection in STAT2 Knockout Hamsters

Abstract: Rift Valley fever virus (RVFV) is an emerging pathogen capable of causing severe disease in livestock and humans and can be transmitted by multiple routes including aerosol exposure. Several animal models have been developed to gain insight into the pathogenesis associated with aerosolized RVFV infection, but work with these models is restricted to high containment biosafety level (BSL) laboratories limiting their use for antiviral and vaccine development studies. Here, we report on a new RVFV inhalation infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Moreover, since the SB strain was generated by multiple passages in the mouse brain, it is likely to be more neuro-adapted than Cl.13, which could explain why the viral loads between the brain and the liver are much higher in the SB-than Cl.13-IN-infected mice (9 vs. 4 log 10 (eqPFU/g)). Previous studies have shown that, in several animal models, an aerosol or IN exposure to RVFV leads mainly to severe neurological symptoms compared to peripheral infection routes [27,29,31,[42][43][44][45][46]. However, most studies have uses virulent RVFV strains at infectious doses that induce rapidly developing severe disease and death, making it difficult to study the impact of administration routes on the virulence and pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, since the SB strain was generated by multiple passages in the mouse brain, it is likely to be more neuro-adapted than Cl.13, which could explain why the viral loads between the brain and the liver are much higher in the SB-than Cl.13-IN-infected mice (9 vs. 4 log 10 (eqPFU/g)). Previous studies have shown that, in several animal models, an aerosol or IN exposure to RVFV leads mainly to severe neurological symptoms compared to peripheral infection routes [27,29,31,[42][43][44][45][46]. However, most studies have uses virulent RVFV strains at infectious doses that induce rapidly developing severe disease and death, making it difficult to study the impact of administration routes on the virulence and pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of STAT2 knockout (KO) animals and naturally occurring mutations in humans have lent further credence to the paramount importance of STAT2 in antiviral immunity. Such reports include but are not limited to the early observation of enhanced VSV virulence in KO (STAT2 –/– ) mice [ 26 ], increased pathogenesis of Rift Valley fever virus [ 27 ] and Crimean-Congo hemorrhagic fever virus [ 28 ], and increased dissemination of SARS-CoV-2 in STAT2 KO hamsters [ 29 ]. In human subjects, heterozygous carriers of STAT2 null mutations are clinically unaffected; however, those with complete loss of STAT2 function showed the interesting phenotype of severe viral disease from live-attenuated virus vaccines, such as those for measles, mumps, and rubella (MMR) and varicella zoster virus [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is a significant risk of death and morbidity in the event that RVF progresses to neurological disease, and not much is known about the pathogenic mechanisms of RVF encephalitis compared to the more extensively studied hepatic disease. In several animal models, respiratory infection by intranasal or aerosol exposure is more likely to lead to encephalitis than OPEN ACCESS peripheral infection routes [12][13][14][15][16][17][18]. Our previous studies have characterized the Lewis rat model of RVF encephalitis, in which rats exposed to aerosolized RVFV succumb to meningoencephalitis within 7-8 days post-infection (p.i.)…”
Section: Introductionmentioning
confidence: 99%